EFEKTIFITAS PENGGUNAAN MEDIA VIDEO BERBASIS LINGKUNGAN (MVBL) DALAMMENINGKATKAN PERILAKU POSITIF ANAK TERHADAP LINGKUNGAN - Widowati Anantasari; A. Wahab Jufri; Aos Santosa Hadiwijaya (Postgraduate, University of Mataram, 2015)
The positive attitude of students toward environment is the manifestation of a positive attitude of students toward the environment. The development of student positive attitude toward environment can be gotten through the aplication of daily attitude and the model that student s catch and feel from the environment where student s live. The students need to get the experiences and learn by themselves with a possitive attitude in order that they are accepted by the environment and they do not do harm their environment. The experiences given to the student should be prepared to help them to share, cooperate, respect, love renponsible, and having self confidance. This research aim at knowing the difference of children’s possitive attitude toward environment at students who lern by using video media based environment (VMBE). Will those who do not learn by using video media based environment (VMBE). Research was aquasi experimental research with pretest and posttest control design. The data of students positive attitude toward environment were gotten by using observation technique ( the observation of students positive attitude improvement ) The data of this research were analyzed by using the analysis of independent sample t-test tecnique.The result of analysis can be concluded as follows : with df : 16 at significant level 0.05 showed that there was difference of students possitive attitude who learn by using MVBL than those who did not learn by using MVBL (t=3.120)Keywords : VMBE, Possitive attitude toward environment.